Representasi Ganbaru pada Anime The Wind Rises (2013) - Putri, Gita Alya Hartono; Ridoewan, Shalsa Dellia; Kresna, Dhimas Wahyu Sri; Faadhila, Salsabila Nur; Fairuzzahra, Nabila Vina (Japanology: The Journal of Japanese Studies, 2024)
Ganbaru is a value that has been deeply rooted in Japanese society, even it has been quite known well globally. Ganbaru is often described as having an attitude of hard work and never giving up. The value of ganbaru has been widely represented through anime. One of them is the anime called The Wind Rises (2013). This research aims to examine the value of ganbaru as depicted through the character Horikoshi Jiro in The Wind Rises. The Wind Rises is an anime film produced by Studio Ghibli which tells the life of Horikoshi Jiro, an airplane designer from Japan during the World War, and his struggle to make an advanced airplane. This research is descriptive qualitative research which uses the ganbaru concept in analyzing the data. The research results show that Jiro displays ganbaru values ​​through the attitudes of 1) working hard and being patient; and 2) insisting of having his way. Thus, it can be understood that Jiro is a representation of ganbaru values ​​in Japanese society.